KUALITAS ORGANOLEPTIK DAN TINGKAT KESUKAAN TELUR ASIN DENGAN ESKALASI KAYU SECANG (Caesalpinia sappan) DAN BAWANG PUTIH (Allium sativum) - Vinata Rahmaningrum; Vian Dwi Chalisty; Aqil Adyatama (Jurnal Agriovet, 2026)
The research conducted aims to determine the effect of sappanwood and garlic escalation on the organoleptic quality and level of preference of salted eggs. The materials used in this study were duck eggs, sappanwood, garlic, bricks, and salt. The experimental design used (CRD) 5 treatments and 5 replications, namely P0 (without sappanwood and garlic), P1: Mix KS and BP 15 grams, P2: Mix KS and BP 30 grams, P3: Mix KS and BP 45 grams, P4: Mix KS and BP 60 grams. The scale seen in this study includes organoleptic tests of color, aroma, taste, texture and level of preference of 30 semi-trained lecturers. Data analysis was carried out using SPSS 26.0 with the Kruskal-Wallis test and the Mann-Whitney test if there is a significant difference. The results of the research conducted were P0 = color (1.94 ± 0.24a), aroma (2.02 ± 0.74a), texture (2.27 ± 0.72a), taste (2.27 ± 0.72c), preference level (2.97 ± 0.48a). P1 = color (2.00 ± 0.00b), aroma (3.28 ± 0.72b), texture (3.05 ± 0.71b), taste (4.27 ± 0.59b), preference level (3.11 ± 0.32b). P2 = color (1.90 ± 0.30a), aroma (3.95 ± 0.81d), texture (4.00 ± 0.67c), taste (3.95 ± 0.71a), preference level (3.65 ± 0.48c). P3 = color (1.99 ± 0.12b), aroma (3.89 ± 0.82d), texture (3.89 ± 0.78c), taste (4.21 ± 0.50b), preference level (4.52 ± 0.50d). P4 = color (1.94 ± 0.24a), aroma (3.61 ± 1.07c), texture (4.05 ± 0.74c), taste (4.07 ± 0.54a), preference level (4.77 ± 0.42e). Based on the research that has been carried out, it can be concluded that salted eggs in P3 with a mix escalation of KS and BP 45 grams are the best treatment because they show the highest aroma, texture, taste and preference level, but have not yet produced the typical color of normal salted eggs. Keywords: salted eggs, sappanwood, garlic, organoleptic quality, preference level